رأسمال المخاطر اتجاه بديل لتمويل المؤسسات الناشئة في الجزائر -عرض تجارب عالمية رائدة- - بن عدة, سمية; بودالي, مخطار (جامعة الوادي - University of Eloued, 2022)
نهدف من خلال دراستنا إلى تسليط الضوء على رأس المال المخاطر كمصدر بديل وفعال لتمويل المؤسسات الناشئة في ظل الصعوبات التي تواجهها في الحصول على تمويل، من خلال تقديم مجموعة من التجارب العالمية الرائدة في هذا المجال، للاستفادة منها و للتعرف على النواقص التي تعاني منها البيئة الجزائرية. وخلصنا إلى أن أهم ما يعيق نجاح تمويل رأس المال الاستثماري في الجزائر هو عدم وجود ثقافة رأس مال المخاطرة بين المقاولين الجزائريين، وطبيعة المؤسسات الجزائرية التي تميل إلى الطابع العائلي، ورفض أصحابها فتح رأس المال ورفض المشاركة فيه، وغياب تدخل الدولة على عكس ما وجدناه في الولايات المتحدة الأمريكية. We aim through our study to shed light on venture capital as an alternative and effective source for financing emerging institutions in light of the difficulties they face in obtaining financing, by presenting a set of leading global experiences in this field, to benefit from them and to identify the shortcomings that the Algerian environment suffers from. . We concluded that the most important thing that hinders the success of investment capital financing in Algeria is the lack of a culture of risk capital among Algerian contractors, the nature of Algerian institutions that tend to be familyoriented, their owners refusal to open capital and their refusal to participate in it, and the absence of state intervention contrary to what we found in United States of America
Risk capital is an alternative direction for financing startups in Algeria-Showcasing worldleading experiences-
مقال
Keywords: رأسمال مخاطر ; مؤسسات ناشئة ; تمويل ; استثمار